A novel sensor to estimate the prevalence of hypochlorous (HOCl) toxicity in individuals with type 2 diabetes and dyslipidemia - Ghoshal, Kakali; Das, Sangita; Aich, Krishnendu; Goswami, Shyamaprosad; Chowdhury, Subhankar; Bhattacharyya, Maitree (Clinica chimica acta, 2016)
Oxidative stress is common in type 2 diabetes. It is characterised by increased levels of reactive oxygen species (ROS), of which hypochlorous acid (HOCl) is an important component. Type 2 diabetes is characterised not only by hyperglycemia, but also by dyslipidemia. It probably underlies both the development of diabetes and also resulting complications, like cardiovascular disease. We applied a novel fluoroprobe RHQ to estimate endogenous HOCl and myeloperoxidase (MPO) activity in diabetes and dyslipidemia. Our newly designed probe, RHQ (rhodamine-quinoline based chemodosimeter) is capable of estimating endogenous HOCl selectively out of the ROS components. Isolated leukocytes from study subjects were treated with DCFDA and monocytes and neutrophils with RHQ for estimating endogenous ROS and HOCl respectively. Plasma AOPP, an indicator of HOCl was also measured. We attempted to find out the key reasons of higher HOCl content in diabetic dyslipidemic subjects by quantitating endogenous hydrogen peroxide (H2O2) and myeloperoxidase (MPO) activity. Isolated PBMCs from diabetic dyslipidemic subjects indicated enhanced ROS and HOCl generation followed by diabetic subjects without dyslipidemia and healthy controls. We explored increased production of H2O2 and enhanced enzymatic activity of myeloperoxidase (MPO) among diabetic dyslipidemic subjects (p<0.0001) resulting in higher HOCl content. The hyperglycemic and hyperlipidemic challenges together enhance the production of HOCl and the fluoroprobe RHQ may be used as a novel diagnostic marker to evaluate the extent of this toxicity.